1996
DOI: 10.1073/pnas.93.24.14199
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana defense-related protein ELI3 is an aromatic alcohol:NADP +  oxidoreductase

Abstract: We expressed a cDNA encoding the Arabidopsis thaliana defense-related protein ELI3-2 in Escherichia coli to determine its biochemical function. . Studies on the substrate specificity now revealed that ELI3-2 is an aromatic alcohol: NADP ؉ oxidoreductase (benzyl alcohol dehydrogenase). The enzyme showed a strong preference for various aromatic aldehydes as opposed to the corresponding alcohols. Highest substrate affinities were observed for 2-methoxybenzaldehyde, 3-methoxybenzaldehyde, salicylaldehyde, and benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 33 publications
2
65
0
1
Order By: Relevance
“…Genes involved in monolignol precursor biosynthesis are found, including genes encoding 4-coumarate CoA ligase (4CL, contig 1516 in Table 1) and caffeoylCoA O-methyltransferase (CCoAOMT, contig 1539 in Table 1). Other genes of less certain relationship to lignin biosynthesis are also highly expressed, such as a gene (contig 1524) very similar to ELI3 of parsley, which encodes a protein with benzyl alcohol dehydrogenase activity (Somssich et al, 1996). At least one transcript encoding a protein similar to laccase is highly abundant, while none of the abundant transcripts encode peroxidases, consistent with findings of pilot-scale EST studies of pine and poplar (Allona et al, 1998;Sterky et al, 1998;Mellerowicz et al, 2001, this issue).…”
Section: What Types Of Genes Are Abundantly Expressed In Wood-formingsupporting
confidence: 70%
“…Genes involved in monolignol precursor biosynthesis are found, including genes encoding 4-coumarate CoA ligase (4CL, contig 1516 in Table 1) and caffeoylCoA O-methyltransferase (CCoAOMT, contig 1539 in Table 1). Other genes of less certain relationship to lignin biosynthesis are also highly expressed, such as a gene (contig 1524) very similar to ELI3 of parsley, which encodes a protein with benzyl alcohol dehydrogenase activity (Somssich et al, 1996). At least one transcript encoding a protein similar to laccase is highly abundant, while none of the abundant transcripts encode peroxidases, consistent with findings of pilot-scale EST studies of pine and poplar (Allona et al, 1998;Sterky et al, 1998;Mellerowicz et al, 2001, this issue).…”
Section: What Types Of Genes Are Abundantly Expressed In Wood-formingsupporting
confidence: 70%
“…The AtCAD-B paralogs corresponding to ELI-3 proteins have been studied previously and were originally identified as part of the defense response in parsley (Petroselinum crispum) and in Arabidopsis (Kiedrowski et al, 1992). Williamson et al (1995) and Somssich et al (1996) demonstrated that ELI-3 was neither a CAD nor a malate dehydrogenase but rather a benzyl alcohol dehydrogenase, which accepts various benzaldehyde substrates. In our phylogenetic analysis, these proteins (AtCAD-A, AtCAD-B1, and -B2) fall within the same cluster as PtSAD, which has been recently identified and characterized in poplar (Li et al, 2001).…”
Section: Atcad-c and Atcad-d Belong To A Small Multigene Family In Armentioning
confidence: 99%
“…However, in most cases, these experiments led to conflicting results. Meanwhile, subsequent in depth analysis suggested unsuspected functions for these proteins (Somssich et al, 1996;Goffner et al, 1998). Together, these studies indicate that, if heterologous protein expression is useful in determining biochemical profiles, other approaches are needed to confirm a biological function.…”
mentioning
confidence: 99%
“…Comparison of the activity profile of M. bovis BCG ADH with those of defence-related (A. thaliana ELI3±2 and P. crispum CAD) and lignification-related (E. gunnii CAD) CADs lead to interesting observations. Firstly, as observed with the M. bovis BCG ADH, processing of alcohols by defence CADs was far less efficient than that of aldehydes as shown by the 50±100-fold decrease in k cat /K m values with A. thaliana ELI3-2 [35] and the absence of alcohol dehydrogenase activity with P. crispum CAD [37]. In contrast, the k cat /K m values of E. gunnii CAD with alcohols were only 2±10-fold lower than those recorded with their corresponding aldehydes [16].…”
Section: Discussionmentioning
confidence: 94%
“…Two potential physiological functions have been attributed to the plant CADs: on one hand, there are enzymes implicated in defence reactions [35] for which the exact role is undetermined (for instance, A. thaliana ELI3±2 and P. crispum CAD) and on the other hand, there are enzymes directly involved in the biosynthesis of the lignin polymer (a cell wall component of higher plants), as exemplified by E. gunnii CAD. Lignins are formed by cell-wall peroxidases that catalyse the polymerization of three phenolic basic units, coniferyl, sinapyl and paracoumaryl alcohols depending on plant species [36].…”
Section: Discussionmentioning
confidence: 99%